The role of clinical nurse specialists in the implementation and sustainability of a practice change. (5th November 2014) - Babine, Rhonda L.; Honess, Cindy; Wierman, Heidi R.; Hallen, Sarah
Abstract : Aim: This project's purpose was to promote and sustain a practice change focusing on delirium utilising the clinical nurse specialist (CNS) in a leadership role. Background: Delirium is an altered state of consciousness accompanied by an acute change in cognition that tends to have a fluctuating course. Delirium is strongly associated with negative outcomes and is often unrecognised. Method: A policy was implemented stating that the RNs will screen patients for delirium with the confusion assessment method (CAM). Interdisciplinary delirium education was offered prior to the practice change and repeated at 3, 6 and 12 months after implementation. The documentation, completion and CAM accuracy screening were determined by the CNS. Results: The CAM documentation and completion audit goal was met and sustained by week 21, and screenings were accurate 83% of the time. Conclusions: The CNS has an opportunity to take a leadership role when instituting an innovative practice change. Successful implementation of a new practice requires that patient care units are divided into cohorts with systematic roll‐out of the initiative. Implications for nursing management: In addition to leadership, CNS availability on the patient care units is imperative to staff acceptance and sustainability of a practice change.